Chromatin architecture: A new dimension in the dynamic control of gene expression - Ramirez-Prado, Juan Sebastian (Plant Signal Behav, 2016)
As the most recent evidence of eukaryotic cell complexity, genome architecture has astounded the scientific community and prompted a variety of technical and cognitive challenges. Several technologies have emerged and evidenced the integration of chromatin packaging and topology, epigenetic processes, and transcription for the pertinent regulation of gene expression. In the present addendum we present and discuss some of our recent research, directed toward the holistic comprehension of the processes by which plants respond to environmental and developmental stimuli. We propose that the study of genome topology and genomic interactions is essential for the understanding of the molecular mechanisms behind a phenotype. Even though our knowledge and understanding of genome architecture and hierarchy has improved substantially in the last few years -in Arabidopsis and other eukaryotes -, there is still a long way ahead in this relatively new field of study. For this, it is necessary to take advantage of the high resolution of the emerging available techniques, and perform integrative approaches with which it will be possible to depict the role of chromatin architecture in the regulation of transcription and ultimately, physiological processes.